Changes in Pulmonary Artery Pressure Late in Life - Zierath, Rani; Claggett, Brian; Arthur, Victoria; Yang, Yimin; Skali, Hicham; Matsushita, Kunihiro; Kitzman, Dalane; Konety, Suma; Mosley, Thomas; Shah, Amil M. (Journal of the American College of Cardiology, 2023)
Although the prognostic implications of higher pulmonary artery systolic pressure (PASP) are well established, few data exist regarding longitudinal change in pulmonary pressure in late life. The aim of this study was to quantify changes in PASP over 6 years and determine the relative contributions of cardiac and pulmonary dysfunction. Among 1,420 participants in the ARIC (Atherosclerosis Risk in Communities) study with echocardiographic measures of PASP at both the fifth (2011-2013) and seventh (2018-2019) visits, longitudinal changes in PASP over about 6.5 years were quantified. Multivariable regression was used to determine the extent to which cardiac and pulmonary dysfunction were associated with changes in PASP and to define the relationship of changes in PASP with dyspnea development. The mean age was 75 ± 5 years at visit 5 and 81 ± 5 years at visit 7, 24% of subjects were Black adults, and 68% were women. Over the 6.5 years, PASP increased by 5 ± 8 mm Hg, from 28 ± 5 to 33 ± 8 mm Hg. PASP increased more in older participants. Predictors of greater increases in PASP included worse left ventricular (LV) systolic and diastolic function, pulmonary function, and renal function. Increases in PASP were associated with concomitant increases in measures of LV filling pressure, including E/e′ ratio and left atrial volume index. Each 5 mm Hg increase was associated with 16% higher odds of developing dyspnea (OR: 1.16; 95% CI: 1.07-1.27; P < 0.001). Pulmonary pressure increased over 6.5 years in late life, was associated with concomitant increases in LV filling pressure, and predicted the development of dyspnea. Interventions targeting LV diastolic function may be effective at mitigating age-related increases in PASP. [Display omitted]